Powtoon Learning Media Containing Local Wisdom Improves Elementary School Social Sciences Learning Outcomes - Devita Dwi Permatasari; Novi Setyasto (Jurnal Edutech Undiksha, 2024)
The lack of social studies learning media has an impact on low student learning outcomes. This research aims to develop powtoon learning media containing local wisdom to improve elementary school social studies learning outcomes. This type of research is Research and Development (R&D) using the Borg and Gall development model.  This research involved media experts and material experts. The test subjects for this research were 26 elementary school IV student participants. Data collection were carried out using interviews, observation, documentation, questionnaires and tests. This research uses questionnaire instruments and test questions in data collection. The data collected was analyzed using qualitative, quantitative, and t-test descriptive analysis. The results of the research show that Powtoon learning media containing local wisdom was declared "very feasible" by media experts with a percentage of 96.8% and a percentage of 95% by material experts. The responses given by students received a percentage of 95% which was included in the "very appropriate" category. The t-test results show a significant difference between the learning outcomes of pre-test and post-test data. It can be concluded that the innovation of Powtoon learning media containing local wisdom in social studies learning, especially class IV economic activities, can improve social studies learning outcomes for class IV students. This research has implications for improving student learning outcomes and the effectiveness of learning through Powtoon media containing local wisdom in social studies learning in elementary schools.